2004
DOI: 10.1091/mbc.e03-06-0388
|View full text |Cite
|
Sign up to set email alerts
|

Repositioning of Muscle-specific Genes Relative to the Periphery of SC-35 Domains during Skeletal Myogenesis

Abstract: Previous studies have shown that in a given cell type, certain active genes associate with SC-35 domains, nuclear regions rich in RNA metabolic factors and excluded from heterochromatin. This organization is not seen for all active genes; therefore, it is important to determine whether and when this locus-specific organization arises during development and differentiation of specific cell types. Here, we investigate whether gene organization relative to SC-35 domains is cell type specific by following several … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
91
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(94 citation statements)
references
References 56 publications
3
91
0
Order By: Relevance
“…Although a body of evidence supports that genes are found on the border of chromosome territories (19,20,(49)(50)(51); specific genes have been shown to express from either inside, on the periphery or well outside of the territory (52)(53)(54). Other reports show that sequences (particularly large clusters of genes) move from a more internal to an external location upon transcriptional activation (53,(55)(56)(57).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a body of evidence supports that genes are found on the border of chromosome territories (19,20,(49)(50)(51); specific genes have been shown to express from either inside, on the periphery or well outside of the territory (52)(53)(54). Other reports show that sequences (particularly large clusters of genes) move from a more internal to an external location upon transcriptional activation (53,(55)(56)(57).…”
Section: Discussionmentioning
confidence: 99%
“…The genes are found outside of the XIST RNA (yellow), which extends beyond the Barr body, the visible manifestation of the heterochromatin. 49,50,58,59) and splicing and transcription factors localize (22,49,51,60,61). The act of silencing and condensing the inner core of Xi may make the existing concentration of protein-coding genes in the peripheral region more pronounced and observable.…”
Section: Discussionmentioning
confidence: 99%
“…This level of nuclear reorganization is often accompanied by a visible level of chromatin decondensation (5, 6, 9). The precise function, if any, of repositioning toward the outside of CTs remains unclear (1), but it may allow for genes to access a nuclear environment enriched in the components of the transcription (10) and/or mRNAprocessing machinery (4,11,12) and so enhance the efficiency of transcription.…”
Section: Inactivation ͉ Y Chromosomementioning
confidence: 99%
“…This level of nuclear reorganization is often accompanied by a visible level of chromatin decondensation (5, 6, 9). The precise function, if any, of repositioning toward the outside of CTs remains unclear (1), but it may allow for genes to access a nuclear environment enriched in the components of the transcription (10) and/or mRNAprocessing machinery (4,11,12) and so enhance the efficiency of transcription.The interplay between this level of higher-order chromatin organization and epigenetic mechanisms that act at primary levels of chromatin structure, such as DNA methylation, is a little-explored area. In plants, changes in the architecture of CTs can be induced by treatment with inhibitors of DNA methylation (13).…”
mentioning
confidence: 99%
“…The combination of genomic sequences and genome-wide expression studies have revealed another form of nonrandom gene distribution, termed tandem gene arrays (TGAs), which represent contiguous stretches of gene loci that display differential regulation during cellular development and/or function (4,5). Importantly, gene clusters and TGAs also demonstrate expression-dependent nuclear localization patterns (6-9); therefore, gene loci are both deterministically arrayed along chromosomes and positioned within the nucleus (10)(11)(12)(13)(14)(15).…”
mentioning
confidence: 99%